Nuevas citas para la provincia de Granada (Andalucía, España). - Navarro, Francisco Bruno; Baena, Laura; Vizoso, M. Teresa (Acta Botanica Malacitana, 2002)
New cites for Granada province (Spain). Palabras clave. Guadix-Baza, corologfa, ecología. Key words. Guadix-Baza, corology, ecology.